MicroRNA miR-34a downregulates FOXP1 during DNA damage response to limit BCR signalling in chronic lymphocytic leukaemia B cells - Cerna, Katerina; Oppelt, Jan; Chochola, Vaclav; Musilova, Katerina; Seda, Vaclav; Pavlasova, Gabriela; Radova, Lenka; Arigoni, Maddalena; Calogero, Raffaele A; Benes, Vladimir; Trbusek, Martin; Brychtova, Yvona; et al. (Leukemia, 2019)
The variable clinical course in chronic lymphocytic leukaemia (CLL) largely depends on p53 functionality and B-cell receptor (BCR) signalling propensity; however, it is unclear if there is any crosstalk between these pathways. We show that DNA damage response (DDR) activation leads to down-modulating the transcriptional factor FOXP1, which functions as a positive BCR signalling regulator and its high levels are associated with worse CLL prognosis. We identified microRNA (miRNA) miR-34a as the most prominently upregulated miRNA during DDR in CLL cells in vitro and in vivo during FCR therapy (fludarabine, cyclophosphamide, rituximab). MiR-34a induced by DDR activation and p53 stabilization potently represses FOXP1 expression by binding in its 3'-UTR. The low FOXP1 levels limit BCR signalling partially via derepressing BCR-inhibitory molecule CD22. We also show that low miR-34a levels can be used as a biomarker for worse response or shorter progression free survival in CLL patients treated with FCR chemoimmunotherapy, and shorter overall survival, irrespective of TP53 status. Additionally, we have developed a method for the absolute quantification of miR-34a copies and defined precise prognostic/predictive cutoffs. Overall, herein, we reveal for the first time that B cells limit their BCR signalling during DDR by down-modulating FOXP1 via DDR-p53/miR-34a axis.
Keywords: následné studie; Female; protokoly protinádorové kombinované chemoterapie; rituximab; lidé středního věku; Repressor Proteins; Vidarabine; forkhead transkripční faktory; Follow-Up Studies; Forkhead Transcription Factors; regulace genové exprese u nádorů; mužské pohlaví; DNA Damage; cyklofosfamid; Biomarkers, Tumor; senioři nad 80 let; Signal Transduction; Humans; dospělí; Antineoplastic Combined Chemotherapy Protocols; Prognosis; MicroRNAs; Survival Rate; nádorové biomarkery; lidé; mikro RNA; míra přežití; Cyclophosphamide; Middle Aged; Rituximab; represorové proteiny; Leukemia, Lymphocytic, Chronic, B-Cell; Aged, 80 and over; senioři; vidarabin; receptory antigenů B-buněk; prognóza; ženské pohlaví; signální transdukce; poškození DNA; Aged; Gene Expression Regulation, Neoplastic; chronická lymfatická leukemie; Adult; Receptors, Antigen, B-Cell; Male